THE EFFECT OF EMPLOYEE SELECTION AND PERFORMANCE ON THE TERMINATION OF EMPLOYMENT OF PT INFOMEDIA NUSANTARA TELKOM MEDAN - Navisa Tan Melyng; Saimara AM Sebayang; Aulia Beywanda Idris; Dastin Syafitri; Dessy Natalia Sianipar (Universitas Efarina, 2021)
PT Infomedia Nusantara is one of Telkom Group's subsidiaries specializing in publishing and advertising media as a communication bridge between business people and also an information channel for telephone customers. The problem in this study is whether selection and performance affect simultaneously or simultaneously the termination of employment at PT. Infomedia Nusantara Telkom Medan. The data collection technique in this study was carried out by questionnaire by distributing a list of questions to respondents as many as 65 respondents through the help of the Statitical Product Service Solution (SPSS) program Version 19.00 Simultaneously or simultaneously Employee Selection and Performance affect Termination of Employment. Partially, independent variables of employee selection and performance have a positive and significant effect on termination of employment. Determination with an adjusted R square of 0.922 means that 92.2% of the variation in termination can be explained by independent variables of selection and performance while the rest (100% - 92.2% = 7.8%) can be explained by other independent variables.